2018
DOI: 10.5897/ajar2017.12743
|View full text |Cite
|
Sign up to set email alerts
|

In support of a well-planned intercropping systems in south eastern soils of Nigeria: A review

Abstract: Soil is the medium for all crop production activities and many of the tropical soils especially soils of South Eastern Nigeria show nutrient deficiency problems after only a short period of cultivation because of the fragile nature and prevailing environmental condition. Land available for further crop production purposes in this area is very limited. To offset some of these problems and boast crop production and yields as well as economic returns, farmers use chemical fertilizers extensively on their field. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Similarly, Alabo et al (2015) reported that 2 rows of sorghum: 1 row of soybean out yielded 1 row of sorghum:1 row of soybean by 83% while soybean yield was 93.3% higher in 1 sorgum:2 rows of soybean than in 1 row of sorgum: 1 row of soybean. In a reviewed paper, Nweke (2017) noted that the Maize/Cowpea intercropping system significantly increased forage dry matter yield compared to maize and cowpea sole crops. In a sorghum/ cowpea intercropped, Afe (2020) observed the lowest grain yield of sorghum (1,160.84 kg/ha) and cowpea (583.38 kg/ha) from 100 sorgum: 100 cowpea and 100 sorghum:25 cowpea population ratios, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Alabo et al (2015) reported that 2 rows of sorghum: 1 row of soybean out yielded 1 row of sorghum:1 row of soybean by 83% while soybean yield was 93.3% higher in 1 sorgum:2 rows of soybean than in 1 row of sorgum: 1 row of soybean. In a reviewed paper, Nweke (2017) noted that the Maize/Cowpea intercropping system significantly increased forage dry matter yield compared to maize and cowpea sole crops. In a sorghum/ cowpea intercropped, Afe (2020) observed the lowest grain yield of sorghum (1,160.84 kg/ha) and cowpea (583.38 kg/ha) from 100 sorgum: 100 cowpea and 100 sorghum:25 cowpea population ratios, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Technically, although crop production aspect involving the application of biological sciences and technology to increase yield and quality of produce play a major role, the agricultural mechanization component of agriculture sector development has been less emphasized or suffered a neglect. Moreover, the common practice of small farm holders in Nigeria is intercropping (Nweke, 2018;Ajayi, 2014) and this is being done using cutlasses and hoes. Efforts must be geared to get over these challenges to achieve the AU agenda 2063.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of intercropping is to produce more crop yield on a piece of land by making use of resources otherwise would not have been utilized by a single crop. This wonderful method of cropping if properly planned and implemented in Nigeria soils especially southeastern region soils taken into account the climate, crop type and variety, disease and pest, as Nweke [8] argued could be a panacea for sustainable food production, environmental harmony and a strong check to land degradation in the area. This new and improved method of cropping advocated has been avoided by farmers especially the large and commercial farmers on the pretense of complications of planting and harvesting.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, intercropping usually give benefit from increased light interception, root contact with more soils and more nutrients, increased microbial activity and can act as a deterrent to pest and weed of the other crop. Available growth resources such as light, water and nutrient are more completely absorbed and converted to crop biomass by the intercropping as a result of differences in competitive ability for growth factor between intercropping components [8,9]. However food production is based on continuous availability of plant nutrients in the soil, and continuous cropping without adequate input and to the depletion of soil nutrients with resultant poor yield of cultivated crops.…”
Section: Introductionmentioning
confidence: 99%